2016
DOI: 10.21315/jcdc2016.21.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Critical Barriers to Implementing Risk Assessment and Management Practices (RAMP) in the Iranian Construction Sector

Abstract: Late completions, frequent work stoppages and cost overruns are common issues in developing countries. Effective risk management (RM) can be utilised to address these common construction issues; however, the uptake of risk management within the Iranian construction industry, as in many developing nations, is limited. This study explored why RM is not used through a questionnaire survey of 90 professionals in the Iranian construction industry. The findings show that professionals in the industry perceive the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 58 publications
0
21
0
1
Order By: Relevance
“…This shortcoming makes the industry loose potential gains inherent in application of risk management procedures [2]. Failure of most construction projects to complete in the agreed time and budget is alleged attributed to risks inherent in construction projects [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…This shortcoming makes the industry loose potential gains inherent in application of risk management procedures [2]. Failure of most construction projects to complete in the agreed time and budget is alleged attributed to risks inherent in construction projects [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…They outlined that SMEs' knowledge and experience in the process have precedence over organisational constraints. This emphasised the viewpoints of Chileshe and Kikwasi [16] that the absence of awareness and experience in tools and techniques are two key innate challenges of professionals in managing risk in construction industry. Therefore, assessing the most beneficial tools and techniques helps SMEs in the practise of risk management and improves business management.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, and finally, examination of Table 1 showed that there was a limited acknowledgement of the relevant PM practices and principles. Therefore, drawing upon similar recommendations by studies such as [88,93] undertaken in developing countries like Tanzania and Iran, there is a clear need of raising the awareness of the importance of these PM practices and principles. Future studies could pursue the extent the integration of these crucial PMBOK areas within the curricula of higher institutions of learning.…”
Section: Structured Framework For Future Studiesmentioning
confidence: 96%